2001
DOI: 10.1902/jop.2001.72.6.774
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antimicrobial Periodontal Treatment on Circulating Tumor Necrosis Factor‐Alpha and Glycated Hemoglobin Level in Patients With Type 2 Diabetes

Abstract: The results indicate that anti-infectious treatment is effective in improving metabolic control in diabetics, possibly through reduced serum TNF-alpha and improved insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
212
5
8

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(247 citation statements)
references
References 21 publications
22
212
5
8
Order By: Relevance
“…These findings were in accordance with the previous studies [10,21]. However, Talbert et al, demonstrated no changes in the TNf-α and IL-6 levels in GCf after non-surgical treatment of periodontitis in type 2diabetic subjects [11].…”
Section: Non-surgical Periodontal Therapy (Srp)-effect On Glycaemic Csupporting
confidence: 93%
See 2 more Smart Citations
“…These findings were in accordance with the previous studies [10,21]. However, Talbert et al, demonstrated no changes in the TNf-α and IL-6 levels in GCf after non-surgical treatment of periodontitis in type 2diabetic subjects [11].…”
Section: Non-surgical Periodontal Therapy (Srp)-effect On Glycaemic Csupporting
confidence: 93%
“…TNf-α level in the serum and gingival crevicular fluid before and after periodontal therapy have shown varying results [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of TNF-a may be associated with increased risk for future development of atherosclerosis in periodontitis patients with type 2 diabetes mellitus. 57,58 TNF-a is closely associated with not only insulin resistance but also with vascular atherogenic changes. 59,60 SOSC genes are positively induced by cytokines.…”
Section: Periodontitis and Aortic Insulin Signaling D Ekuni Et Almentioning
confidence: 99%
“…Therefore, it was hypothesized that DM-induced exaggeration of host immune responses played a crucial role in periodontal pathogenesis 12) , as glucose-mediated advanced glycation end products can increase the production of proinflammatory cytokines and mediators, which could contribute to periodontal destruction 22) . Periodontal disease may also affect blood glucose levels in diabetic patients through insulin resistance 5) . There has been a recent focus on understanding the negative influences of oral chronic inflammation on systemic health 10,12) .…”
Section: Introductionmentioning
confidence: 99%